Brazil’s Maria da Penha Domestic Violence Police Patrols: A Second-Response Innovation in Preventing Revictimization - Macaulay, Fiona (Journal of contemporary criminal justice, 2022)
This article examines an innovative domestic violence intervention: some 300 “second-response” police patrols set up since 2015 by military police forces and municipal guards in cities around Brazil. They enforce court-issued protection orders by paying repeat visits to women at high risk, referring them to support services, and ensuring abusers stay away. Drawing on interviews with officers who founded or now lead these patrols, and on local-level police data and studies, the article analyzes their origins and modus operandi and evaluates their impacts on victims, abusers, the community, and internal police force culture. Available evidence shows that victims enrolled in these programs are much less likely to suffer repeated assault or feminicide than those who are not. The article examines how this intervention fits with the other elements of local protection networks and compares these patrols with second-response police interventions developed elsewhere.